Serrated lesions and polyps of colon - Krsteska, Blagica; Angelovska, Tamara; Risteski, Vladimir; Kostadinova Kunovska, Slavica (Macedonian Society of Gastroenterohepatology, 2023)
Introduction: Serrated lesions and polyps are characterized by the unique architectural pattern of epithelial infoldings into the gland lumen creating a sawtooth (“serrated”) type appearance. Most serrated polyps are asymptomatic and therefore are incidental endoscopic finding. There are 4 main histologic types: hyperplastic polyps, sessile serrated lesion, sessile serrated lesion with dysplasia and traditional serrated adenoma. As many as 30% of colorectal carcinomas arise from serrated neoplasia pathway. Material and methods: Our study analyzed serrated lesions in a one-year period (2022) diagnosed at Institute of pathology, Faculty of medicine in Skopje. Polypectomies were performed at the University Clinic of Gastroenterohepatology in Skopje. All polyps were formalin fixed, paraffin embedded and the sections were routinely stained with HE. Results: We had 99 cases of serrated polyps of colon of which 49 cases were hyperplastic polyps and 50 were sessile serrated lesions. Twenty-seven cases of hyperplastic polyps were males and 22 were females. Thirty-one males had sessile serrated lesions and 19 were females. There were 26 cases of serrated lesions with dysplasia and 24 without dysplasia. Sixteen patients had associated another type of lesion, the most common was conventional tubulovillous adenoma. Conclusion: Serrated lesions in our study were more common in males. Small hyperplastic polyps in distal colon have no malignant potential. Dysplasia was found in almost half of the cases with serrated lesions. Although most of the serrated lesions contain no dysplasia, missing serrated polyp with dysplasia on endoscopy may increase the risk for postcolonoscopy cancer. Follow up intervals are recommended especially in large serrated polyps (>1cm) because of the risk for colorectal carcinoma.
Keywords: sessile serrated lesion